2016
DOI: 10.1177/1756285616641583
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous immunoglobulins in the treatment of chronic immune-mediated neuropathies

Abstract: Abstract:Intravenous immunoglobulins represent an established therapy for the treatment of chronic immune-mediated neuropathies, specifically chronic inflammatory demyelinating polyradiculoneuropathies (CIDPs) as well as multifocal motor neuropathies (MMNs). For the treatment of antibody deficiency syndromes, subcutaneous immunoglobulins (SCIgs) have represented a mainstay for decades. An emerging body of evidence suggests that SCIg might also exhibit clinical efficacy in CIDP and MMN. This article reviews the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
0
11
0
3
Order By: Relevance
“…Beim Umsetzen sollte zunächst eine der intravenösen Gabe äquivalente Dosis appliziert werden. Weitere Langzeituntersuchungen zum Einsatz von SCIG bei MMN sind jedoch noch erforderlich [57]. Evidenzklasse: II; Empfehlungsklasse: B.…”
Section: Subkutane Immunglobulineunclassified
See 1 more Smart Citation
“…Beim Umsetzen sollte zunächst eine der intravenösen Gabe äquivalente Dosis appliziert werden. Weitere Langzeituntersuchungen zum Einsatz von SCIG bei MMN sind jedoch noch erforderlich [57]. Evidenzklasse: II; Empfehlungsklasse: B.…”
Section: Subkutane Immunglobulineunclassified
“…Es besteht weiterhin Bedarf an kon trollierten Studien, die eine Langzeitwirksamkeit von SCIG bei der CIDP demonstrieren. Dabei gilt es die optimale Dosierung zu definieren[57].…”
unclassified
“…1 Subcutaneous immunoglobulin (SCIg) has gained popularity as it is a less invasive procedure and can be selfadministered at home for both patients with primary and secondary immunodeficiency and immune-mediated neurological disorders. 2,3 A recent systematic review and meta-analysis confirmed that SCIg treatment was as effective as IVIg treatment in patients with primary immunodeficiency, and had fewer associated side-effects. 4 Our group previously reported that SCIg was an effective adjunctive therapy for the chronic management of myasthenia gravis (MG), identified by high patient satisfaction on several assessment scales.…”
Section: Introductionmentioning
confidence: 99%
“…5 Many studies also suggested SCIg as a viable alternative to IVIg in the management of chronic inflammatory demyelinating polyneuropathy (CIDP) and multifocal motor neuropathy (MMN). 3,[6][7][8] SCIg is also recently approved to be used as maintenance therapy to prevent relapse of neuromuscular disability and impairment in patients with CIDP following the PATH study. 8 Research has shown that patients can be effectively switched from IVIg to SCIg without deterioration in their symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Die subkutane Verabreichung von Immunglobulinen wird auch von Patientenseite oft gegenüber der intravenösen Applikation bevorzugt, da eine höhere Patientenautonomie mit Vermeidung von Krankenhausaufenthalten und damit insgesamt eine verbesserte Lebensqualität besteht[17,20]. Die Sicherheit, Umsetzbarkeit und klinische Effektivität der subkutanen Immunglobulintherapie bei Patienten mit CIDP wurde in mehreren Fallserien und Studien gezeigt[17,[19][20][21][22][23][24]. In der bisher größten randomisierten Phase-III-Studie erhielten 172 Patienten mit CIDP, welche unter IVIG-Therapie einen stabilen klinischen Zustand erreicht hatten, Placebo oder SCIG in einer Dosis von entweder 0,2 g/kg KG oder 0,4 g/kg KG wöchentlich über 24 Wochen[4].…”
unclassified